2018
DOI: 10.24036/rapun.v9i2.102216
|View full text |Cite
|
Sign up to set email alerts
|

Pelatihan Pendidikan Seksual Untuk Meningkatkan Pengetahuan Tentang Seksualitas Anak Pada Guru Di Kab. Tanah Datar

Abstract: Abstact: Sexual education training to improve teacher child sexuality. As many cases of sexual abuse among the elementary school age, there is a need too have the prevention program for the case. This training was aimed at giving knowledge about child sexuality for elementary school teachers in Tanah Datar Regency, West Sumatera Province, Indonesia. This study used quasi experimental with one group pretest-posttest design. There were 61 participants participating in this study. The data were analyzed using tte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…As a result, this approach is well-suited for use in the synthesis of metal materials such as zinc (Zn), titanium (Ti), and iron (Fe) [100]. In the product creation process, the coprecipitation process requires managing the pH, temperature, and stirring speed [110]. According to Ningsih [110], this method has two advantages: (1) homogenization of the reactant sediment to reduce temperature and (2) a longer process to detect metal oxide powder.…”
Section: Coprecipitation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, this approach is well-suited for use in the synthesis of metal materials such as zinc (Zn), titanium (Ti), and iron (Fe) [100]. In the product creation process, the coprecipitation process requires managing the pH, temperature, and stirring speed [110]. According to Ningsih [110], this method has two advantages: (1) homogenization of the reactant sediment to reduce temperature and (2) a longer process to detect metal oxide powder.…”
Section: Coprecipitation Methodsmentioning
confidence: 99%
“…In the product creation process, the coprecipitation process requires managing the pH, temperature, and stirring speed [110]. According to Ningsih [110], this method has two advantages: (1) homogenization of the reactant sediment to reduce temperature and (2) a longer process to detect metal oxide powder. The method then has three flaws: (1) it is not fast enough to create material with a high purity, (2) it does not run smoothly because the reactant used is not consistent, and (3) it lacks a universal symbiotic condition for the creation of several metal oxide.…”
Section: Coprecipitation Methodsmentioning
confidence: 99%
“…Hasil penelitian ini sejalan dengan penelitian yang menyatakan bahwa terdapat peningkatan pengetahuan yang bermakna setelah dilakukan pelatihan tentang kekerasan seksualitas pada anak usia dini [9] [10]. Hal ini menunjukan bahwa pelatihan sangat berpengaruh terhadap peningkatan pengetahuan.…”
Section: Hasil Dan Pembahasanunclassified
“…Based on the interviews with parents and teachers, it can be concluded that discussing and teaching sex with children is confusing because sex is sensitive (Ningsih, 2018).…”
Section: Introductionmentioning
confidence: 99%